Exercise training in heart failure: role, prescription and program - Pranata, Raymond; Yonas, Emir; Siswanto, Bambang B.; Purwowiyoto, Budhi S. (The Indonesian Heart Association, 2017)
Heart failure is one of the most common cardiovascular diseases and is a final pathway of various cardiac pathologies. Exercise intolerance and dyspnea accompanied by deteriorating quality of life are common issues in those suffering from heart failure and may persist despite optimal medical therapy. Exercise training in heart failure theoretically helps to slow down the deterioration of the heart by antagonizing excess neurohormonal activity in heart failure, which translated into better functional capacity and quality of life. Exercise prescription is a mean of assessing and interpreting clinical information and applying the principles of training to develop an appropriate regimen and should be tailored to patient’s clinical condition. Resistance training improves peak VO2, exercise capacity and quality of life in heart failure patients. Both continuous and interval exercise training are linked to better quality of life despite ambiguous results in mortality. The aim of this article is to discuss the benefits of exercise in patients with congestive heart failure, exercise prescription, and exercise program including high-intensity interval training, continuous training and resistance exercise.   Abstrak Gagal jantung adalah salah satu penyakit kardiovaskular yang paling sering ditemui dan merupakan akhir daripada banyak jenis patologi jantung. Intoleransi olahraga dan sesak nafas disertai dengan memburuknya kualitas hidup merupakan beberapa masalah yang sering dihadapi oleh pasien gagal jantung, meskipun telah diberikan pengobatan yang optimal. Latihan olahraga pada gagal jantung secara teoritis dapat memperlambat menurunnya fungsi jantung dengan melawan aktivitas neurohormonal yang meningkat pada kondisi gagal jantung yang dicerminkan dengan kapasitas fungsional dan kualitas hidup yang lebih baik. Preskripsi olahraga meliputi pemeriksaan dan interpretasi dari informasi klinis dan aplikasi dari prinsip latihan untuk membentuk regimen yang sesuai dan harus di sesuaikan dengan keadaan klinis pasien. Latihan beban memperbaiki fungsi VO2 puncak, kapasitas olahraga dan kualitas hidup pada pasien dengan gagal jantung. Kedua metode olahraga baik secara kontinu ataupun interval dihubungkan dengan kualitas hidup yang lebih baik meskipun masih ambigu dalam hal mortalitas. Tujuan artikel ini adalah membahas manfaat latihan fisik pada pasien dengan gagal jantung kongestif, cara peresepan serta membahas program high intensity interval training, continuous training serta latihan beban.